Building Regional Innovation System Policy for Smart City Through E-Health Program in Depok City - Feny Darwati; Rachma Fitriati (Majapahit Journal of Islamic Finance and Management, 2026)
Urbanization and technological disruption require digital transformation within local government. Depok City has demonstrated a commitment to becoming a Smart City through its Regional Innovation System (RIS), with a particular focus on e-health. This study analyzes existing RIS policies and e-health initiatives, identifies barriers to implementation, and develops an integrated policy model using qualitative Soft Systems Methodology (SSM). Data collection included in-depth interviews with 15 key informants, non-participant observation at three community health centers and one hospital, document analysis, and focus group discussions using the Nominal Group Technique. Findings show that Depok City's Regional Innovation Index (IID) reached 51.12 (classified as innovative) with a budget realization rate of 97.21%. Despite this, e-health implementation remains incomplete. The most significant gaps are in digital standards (79%), digital policies (72%), and digital strategy (68%). Barriers identified include fragmented authority, resistance from senior medical staff, limited infrastructure (internet speeds of 5-15 Mbps), and the absence of personal data protection regulations. The proposed policy model consists of three pillars: a digital strategy (Depok Sehat Digital 2030), digital policies (covering data protection, minimum service standards, incentives, sanctions, and mass literacy), and technical digital standards based on HL7 FHIR. A draft Mayoral Regulation has been prepared. This study advances Digital Governance theory in regional innovation and offers practical recommendations for local governments.